ФОРМУВАННЯ ЯКОСТЕЙ ОСОБИСТОСТІ МАЙБУТНЬОГО ВЧИТЕЛЯ МУЗИКИ У ПІДГОТОВЦІ ДО ДІЯЛЬНОСТІ з ДОБОРУ МУЗИЧНОЇ ІНФОРМАЦІЇ (Педагогіка вищої та середньої школи, 2009)
This article discusses some aspects of the preparation of future teachers of music to work on the selection of musical information, by creating a set of his personal qualities.